Studies on production of Chitosan-alginate capsules through extrusion dripping method - Ong Hui Yen (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
Production of capsules through extrusion dripping method is a simple and low cost method. Chitosan and alginate are common biopolymers used for in the formation of capsules in wide range of industries. However, there is less study done for the formation of capsules with chitosan as inner core material and alginate as shell material by extrusion dripping method. Chitosan-alginate capsules were produced by extruding chitosan-calcium chloride solution into sodium alginate solution. The purpose of this project was to investigate the effects of process variables such as concentration of gel-forming solutions, needle size, gelation time, depth of gelation bath as well as speed of motor stirrer on size and shape chitosan-alginate capsules produced through extrusion dripping method. It was found out that concentration of gel-forming solutions and gelation time has significant effect on size of capsules formed. Under the tested conditions, chitosan-alginate capsules with diameter in a range of 3.16 ± 0.23 mm to 5.73± 0.14 mm were produced. On the other hand, the shape of capsules was significantly affected by the speed of motor stirrer. The result showed sphere capsules up to 90% (with spherical factor <0.07) were produced by the speed of 400rpm and above. Lastly, a diagram based on dimensionless number correlation was developed to determine process variables that can produce spherical chitosan-alginate capsules.